2020
DOI: 10.1089/whr.2020.0085
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Maternal/Fetal Attachment, and Maternal Mental Health

Abstract: Background: This pilot study investigated the potential impact of exposure to childhood adversity on variables known to be related to posttraumatic stress (including attachment, mental health, and perceived stress) in a clinic sample of pregnant women. Materials and Methods: Participants consisted of 101 pregnant women recruited from the Virginia Commonwealth University Health System in Richmond, VA. All participants completed the Adverse Childhood Experience (ACE) ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In general, we found a tight ACEs–ASPD association in our study, which is consistent with previous studies [ 17 , 18 ]. Werner et al found that ASPD has a common genetic basis, which makes ASPD in different backgrounds show similar patterns [ 68 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In general, we found a tight ACEs–ASPD association in our study, which is consistent with previous studies [ 17 , 18 ]. Werner et al found that ASPD has a common genetic basis, which makes ASPD in different backgrounds show similar patterns [ 68 ].…”
Section: Discussionsupporting
confidence: 94%
“…Results also indicated that PAN might lead to mother negative loving perceived by children, indicating that maltreatment from both parents experienced by children may damage the child’s attachment to the mother. This result was consistent with a meta-analysis study which found a robust relationship between ACE and insecure attachment [ 18 , 51 ]. Attachment theory can also explain that primary caregivers’ response to a child’s attachment needs is the key to children’s development of a sense of security, which is a sign of a secure attachment for children [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the effect of ACEs on mental health is cumulative, meaning that exposure to a greater number of ACEs increases the risk of later mental health problems ( 3 ). Research from the parental literature that focused on maternal ACEs similarly found that mothers’ ACEs predicted their depression, anxiety, PTSD ( 6 , 29 , 30 ), and suicidal ideation ( 31 ).…”
Section: Introductionmentioning
confidence: 99%